Meteorological dataset collected by an automatic weather station in the western part of the municipality of Naples (Fuorigrotta, Naples, Italy) during January-December 2022 period - Alberto Fortelli; Giuseppe Ascione; Francesco De Paola; Francesco Pugliese; Giuseppe Speranza; Maurizio Giugni (PANGAEA, 2023)
Weather data monitoring is ongoing since 2020 in two sites located in the urban area of the municipality of Naples. The aim of this activity, developed thanks to DICEA CIRES WATER funds, is to acquire time series of the most relevant meteorological parameters contributing to local scale climate (temperature, wind, rain) so to analyze the Urban context and the physical processes there occurring, such as Urban Heat Island or flash floods. The final goal is to understand how these processes influence the confort and safety of the population in a urban context in order to find solutions to improve the livability in indoor and outdoor space.